Body size and evolutionary rate analyses reveal complex evolutionary history of Alvarezsauria - Meso, Jorge Gustavo (2024)
Some of the smallest examples of dinosaurian body size are from alvarezsaurians, an enigmatic group of maniraptoran coelurosaurians with a peculiar combination of anatomical features unique among theropods. Despite the large number of alvarezsaurian species described worldwide and the increased understanding this has provided, the body-size macroevolution of alvarezsaurians has received little attention. Here we reconstruct and analyse directional trends of alvarezsaurian body-size evolution through an integrated analysis of body mass, ontogenetic age, and morphological rate data enabled by a comprehensively revised phylogeny. Our analyses identify four periods of high morphological rate evolution (Bathonian–Callovian, Hauterivian–early Berriasian, early Cenomanian, and late Cenomanian–Turonian) that we link to the key effects of animal body-size changes for the first time, including morphological novelty, structural reduction and simplification, elevated homoplasy, and behavioral changes associated with miniaturization. In doing so, this study provides a holistic example of miniaturization in a Mesozoic vertebrate group that offers a framework for other detailed studies of animal body-size evolution, including in more disparate groups.